2015
DOI: 10.1038/nrneph.2014.247
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic biomarkers in kidney disease: issues in development and implementation

Abstract: Proteomic biomarkers offer the hope of improving the management of patients with kidney diseases by enabling more accurate and earlier detection of renal pathology than is possible with currently available biomarkers, serum creatinine and urinary albumin. In addition, proteomic biomarkers could also be useful to define the most suitable therapeutic targets in a given patient or disease setting. This Review describes the current status of proteomic and protein biomarkers in the context of kidney diseases. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 134 publications
1
96
0
3
Order By: Relevance
“…We and others have shown that urine is a rich and non-invasive source of biomarkers of disease in humans [17][18][19] . Mass spectrometry-based analysis of the endogenous urinary peptidome (i.e., 5 not generated by trypsin digestion) allows the assessment of thousands of urinary peptides at once.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that urine is a rich and non-invasive source of biomarkers of disease in humans [17][18][19] . Mass spectrometry-based analysis of the endogenous urinary peptidome (i.e., 5 not generated by trypsin digestion) allows the assessment of thousands of urinary peptides at once.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry-based analysis of the endogenous urinary peptidome (i.e., 5 not generated by trypsin digestion) allows the assessment of thousands of urinary peptides at once. Combined in multi-molecular classifiers of tens to hundreds of peptides, these urinary peptides have proven their ability to faithfully describe complex diseases including kidney disease 17,20 , cardiovascular disease 21 , graft-versus-host disease 22 , and cholangiocarcinoma 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Those are the main reasons why the urine is widely used for proteomic biomarkers discovery [17,23,24]. Single-protein biomarkers are not effective and suitable to reflect complex diseases, such as CKD and therefore combination and simultaneous use of multiple biomarkers should improve the diagnostic performance [4,17,25]. Combination of multiple biomarkers in high-dimensional classifiers, substantially outperform linear combination of biomarkers [26].…”
Section: Urinary Biomarkersmentioning
confidence: 99%
“…Currently used diagnostic and staging tools are mostly based on non-invasive analysis of serum creatinine and/ or urinary albumin and estimation of glomerular filtration rate (eGFR). These biomarkers although widely accepted, frequently fail to identify patients at higher risk of progression or death [3,4]. They are also not reliable parameters for early diagnosis, as rising of serum creatinine levels above normal is only evident after substantial loss of renal function and its level may be affected by additional factors, such as the loss of muscle mass [5].…”
Section: Introduction -Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation